Analisis Penyebab Reject Sparepart Mesin Diesel Dengan Metode Fishbone dan FMEA pada PT. Kubota Indonesia - Wibawa, Rama Anugrah; Hartono, Ridwan (Jurnal Teknik Industri Terintegrasi (JUTIN), 2025)
Quality is one of the important factors in the production process. Damaged or defective products cause significant losses to the company. In this study, defective products are products that do not meet the quality standards that have been set during the manufacturing process. When customers feel that the product cannot be used according to their needs, the product will be estimated as a defective product. This research uses the fishbone method, which is more comprehensive than other methods, because it can cover the causal factors of consequences clearly and in detail. Failure Mode and Effects Analysis (FMEA) method to evaluate the risk of failure at the production stage with a quantitative approach. With the application of these two methods, it is expected to analyze the problem quickly, precisely and focus on the cause effectively. Data is collected through direct observation (primary data) and interviews with employees (second data). The results of this study are expected to enable the company to identify and improve the quality of products to be produced in the future.